Proceedings of the 2019 2nd International Conference on Sensors, Signal and Image Processing 2019
DOI: 10.1145/3365245.3365246
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Human Behavioural Consistency by Analysing Periodicity of Household Water Consumption

Abstract: People are living longer than ever due to advances in healthcare, and this has prompted many healthcare providers to look towards remote patient care as a means to meet the needs of the future. It is now a priority to enable people to reside in their own homes rather than in overburdened facilities whenever possible. The increasing maturity of IoT technologies and the falling costs of connected sensors has made the deployment of remote healthcare at scale an increasingly attractive prospect. In this work we de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Determining anomalous behaviors in water consumption is also a major task in water analytics. For example, in [7], changes in household water consumption are identified from water usage readings with the aim of detecting anomalies that may lead to the discovery of manipulated meters. Similarly, [8,9] propose two different approaches for determining anomalous behaviors in water consumption: punctual anomalous consumption and anomalous changes in behavior of water consumption, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…Determining anomalous behaviors in water consumption is also a major task in water analytics. For example, in [7], changes in household water consumption are identified from water usage readings with the aim of detecting anomalies that may lead to the discovery of manipulated meters. Similarly, [8,9] propose two different approaches for determining anomalous behaviors in water consumption: punctual anomalous consumption and anomalous changes in behavior of water consumption, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…Considering the influence of interest change factors on human behaviour, Han et al [12] proposed an adaptive interest-driven model. Quinn et al [13] analyzed the periodicity of water consumption readings collected from water meters of prominent households every 15 minutes for more than eight months and found that periodicity also existed in people's water use behaviour.…”
Section: Introductionmentioning
confidence: 99%